2007
DOI: 10.11646/zootaxa.1553.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Stomatopod and decapod crustaceans from Camamu Bay, state of Bahia, Brazil

Abstract: Camamu Bay, located on the central coast of the state of Bahia, Brazil (13°47’ to 14°10’S), is the third-largest Brazilian bay. It is included in a zone that perhaps constitutes the last unexplored frontier on the Brazilian coast, situated between Todos os Santos Bay in Bahia, and the city of Vitória in Espírito Santo. Moreover, this zone coincides with an area of remarkable zoogeographical interest, the transition zone between the Brazilian and Paulista provinces. Camamu Bay contains a wide diversity of marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…Hence, it is essential to investigate these species in order to conduct any further study and/or planning towards the conservation of estuary regions (Almeida et al, 2007). The situation is even worse regarding places in Northern and North-eastern Brazil, where many locations and environments have not yet been surveyed faunistically (Lana et al, 1996).…”
Section: N T R O D U T I O Nmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, it is essential to investigate these species in order to conduct any further study and/or planning towards the conservation of estuary regions (Almeida et al, 2007). The situation is even worse regarding places in Northern and North-eastern Brazil, where many locations and environments have not yet been surveyed faunistically (Lana et al, 1996).…”
Section: N T R O D U T I O Nmentioning
confidence: 99%
“…A literature review on the faunal and taxonomic studies conducted in these environments has shown that researchers mainly investigate specific groups, such as crustaceans (Severino-Rodrigues et al, 2001;Almeida et al, 2007), bivalves (Fiori, 2007), gastropods (Vasconcelos et al, 2004;Fiori, 2007;Ourives, 2007), nematodes (Fiori, 2007), polychaetes (Vasconcelos et al, 2004;Fiori, 2007), leeches (Fiori, 2007), cnidarians (Mesquita et al, 2006;Fiori, 2007) and fishes (Ramos & Vieira, 2001;Loebmann & Vieira, 2005;Falcão et al, 2006).…”
Section: N T R O D U T I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Decapod crustaceans are important members of tropical benthic communities, some species of larger size have economic interest as food source for humans, but a great variety of small species, such as caridean shrimps, contribute to the functioning of tropical ecosystems (Bauer, 1985;Almeida et al, 2007). The systematic composition of the local assemblages of these organisms has been studied in various tropical regions, including the coasts of Mexico (Markham et al, 1990;Hernández Aguilera et al, 1996;Wicksten & Hendrickx, 2003).…”
Section: Introductionmentioning
confidence: 99%